2017
DOI: 10.5853/jos.2016.00570
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability and Mortality of Patients with Stroke and Active Cancer: The OASIS-CANCER Study

Abstract: Background and PurposePatients with active cancer are at an increased risk for stroke. Hypercoagulability plays an important role in cancer-related stroke. We aimed to test whether 1) hypercoagulability is a predictor of survival, and 2) correction of the hypercoagulable state leads to better survival in patients with stroke and active cancer.MethodsWe recruited consecutive patients with acute ischemic stroke and active systemic cancer between January 2006 and July 2015. Hypercoagulability was assessed using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 38 publications
15
109
0
4
Order By: Relevance
“…56, 74, 75 However, anticoagulation also has drawbacks, especially the increased risk of bleeding, which might outweigh any potential reductions in recurrent thromboembolism risk. This is particularly relevant for cancer patients, who already face up to a 20% annual major bleeding risk.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…56, 74, 75 However, anticoagulation also has drawbacks, especially the increased risk of bleeding, which might outweigh any potential reductions in recurrent thromboembolism risk. This is particularly relevant for cancer patients, who already face up to a 20% annual major bleeding risk.…”
Section: Treatmentsmentioning
confidence: 99%
“…73 In support of anticoagulation for cancer-related stroke are data from small retrospective studies demonstrating reductions in recurrent events, D-dimer levels, and transcranial Doppler microembolism with treatment. 56,74,75 However, anticoagulation also has drawbacks, especially the increased risk of bleeding, which might outweigh any potential reductions in recurrent thromboembolism risk. This is particularly relevant for cancer patients, who already face up to a 20% annual major bleeding risk.…”
Section: Secondary Stroke Preventionmentioning
confidence: 99%
“…We found that the age, as anticipated, was a strong predictor of mortality in patients aged ≥65 years and were at a 5.9‐fold greater risk of death than those aged <65 years after a first‐ever TIA, in concordance with a previously published study (van Wijk et al., ). The prevalence of heart failure, dementia, stroke, chronic kidney disease, and anemia are common among patients with stroke and confer increased mortality (Barba et al., ; Desmond, Moroney, Sano, & Stern, ; Divani, Vazquez, Asadollahi, Qureshi, & Pullicino, ; Lee et al., ; Sharma, Fletcher, Vassallo, & Ross, ; Strachan, ; Wannamethee, Shaper, & Ebrahim, ). We recently reported that a number of comorbid CCs were associated with 30‐day postdischarge mortality in patients with initial stroke and TIA (Yousufuddin et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to D-dimer levels, several groups have studied D-dimer as a marker of a cancer-associated hypercoagulable state and in some cases high levels of D-dimer have been correlated with an increased risk of early recurrent events in patients with cancer after an initial acute ischaemic stroke. [13][14][15][16][17][18] However, it is important to note that the predictive utility of this biomarker is not always this straightforward. This is because D-dimer levels could also be influenced by the advanced malignancy itself (such as large tumour burden, progression and metastasis without thrombosis), increased age, diabetes and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…novel treatment (new drug/intervention; established drug/procedure in new situation) and a predictor of the short-term risk of ischaemic strokes in cancer patients. [13][14][15][16][17][18][19][20] In cancer-associated thrombosis, the Khorana score is the most validated method that helps to assess venous thromboembolism (VTE) risk in cancer outpatients receiving chemotherapy and to inform recommendation for thromboprophylaxis. 21 22 The calculated Khorana score for our patient using baseline data at the time of chemotherapy was 1 point (body mass index >35 kg/ m 2 ) for an intermediate VTE risk of 1.8%-2.0% at 2.5 months.…”
Section: Ischaemic Stroke Associated With the Chemotherapy Agentsmentioning
confidence: 99%